Is Radha’ah Obligatory? An Interpretive Perspective on Qs. Al-Baqarah Verse 233: Systematic Literature Review Analysis - Nidaul Fauziah; Ahmad Isnaeni; Nurul Isnaini (Jurnal test, 2026)
This study examines the obligation of radha’ah (breastfeeding) in the exegetical perspective of QS. Al-Baqarah verse 233 using the Systematic Literature Review (SLR) method. The research process consisted of systematic stages of identification, screening, and selection of relevant literature. Article searches were conducted using the Publish or Perish (PoP) application with PCC based keywords: “radha’ah,” “breastfeeding mothers,” and “tafsir of Al-Baqarah 233.” The initial search produced 7,507 articles from Google Scholar, Semantic Scholar, and JSTOR. These articles were screened using PRISMA procedures and analyzed through Rayyan.ai based on inclusion and exclusion criteria, resulting in 13 articles eligible for further analysis. Thematic relationships among the literature were visualized using VOSviewer, which revealed major clusters related to radha’ah, breastfeeding obligations, infant nutrition, and the exegesis of QS. Al-Baqarah 233. The findings indicate that most mufassir interpret the amr form in the verse as an obligatory command for mothers, considering that breast milk is a biological consequence of pregnancy and the primary source of nutrition for infants. Some scholars view it as recommended in certain conditions, yet the literature consistently affirms that radha’ah is a fundamental right of the child and aligns with the maqasid al-shari’ah, particularly hifz al-nafs and hifz al-nasl. This study underscores the verse’s relevance to modern health issues and strengthens the comprehensive understanding of radha’ah in the Islamic perspective.